The Effect of Employee Competence on Distribution Efficiency in Logistics Management at PT. - Yusup Rachmat Hidayat; Muhammad Raka Aldriansyah; Elvin Suwarso (Universitas Lambung Mangkurat, 2025)
This research was conducted on PT. Intek Indonesia Solution with the aim of determining the influence of employee competence on distribution efficiency in logistics management. This study is a quantitative research withan exploratory measurement method. The data collection technique was used by distributing questionnaires. The population in this study includes all 116 employees involved in logistics management at PT. Intek Indonesia Solutions includes operational staff, supervisors, and managers involved in the distribution process. An example of the criteria in this study is employees who have worked for the company for more than one year. Based on the results of the study, it can be concluded that employee competence has a positive and significant influence on distribution efficiency at PT. Intek Indonesia Solutions. From the Determination Coefficient (R Square) shows a value of 0.68 or 68%, meaning that this value shows that the employee competency variable has an influence on the distribution efficiency variable by 68% and the remaining 32% is influenced by other variables that are not studied in this study.